The 5‐HT1A receptor agonist, 8‐OH‐DPAT, attenuates long‐lasting pain in imiquimod‐induced psoriasis in mice. Issue 4 (10th November 2021) - Cervantes‐Durán, Claudia; Avalos‐Viveros, Miguel; Torner, Luz; Sánchez‐Ceja, Sandra‐Guadalupe; Rodríguez‐Orozco, Alain‐Raimundo; Martínez‐Flores, Héctor‐Eduardo; García‐Pérez, Martha‐Estrella
Abstract: Psoriasis pain is a common symptom underestimated and rarely evaluated in psoriasis clinical trials. This work aimed to investigate whether the development of secondary chronic allodynia and hyperalgesia in the imiquimod (IMQ)‐induced psoriasis mice model could be modulated by anti‐inflammatory agents and compound 48/80 (C48/80) and to determine whether the activation of 5‐HT1A receptor modulates these nociceptive behaviours. C57BL/6 male mice were treated with 5% IMQ for 7 days. The paw withdrawal responses to von Frey filaments (10 and 250 mN) were used to assess the allodynia and hyperalgesia. Nociceptive behaviours were also evaluated using ketorolac 15 mg/kg s.c., adalimumab 10 mg/kg s.c. and C48/80 10 mg/kg i.p. Then, the serum serotonin and the impact of 8‐OH‐DPAT (1 mg/kg s.c), a 5‐HT1A receptor agonist, on long‐lasting pain were examined. Mice receiving IMQ showed enhanced nociception, which decreased with all tested compounds. The serum serotonin in the IMQ group showed a significant decrease (947.042 ng/ml) regarding the control group (1143.68 ng/ml). The pretreatment with 8‐OH‐DPAT alleviated pain‐related behaviours. These results suggest that the long‐lasting pain resulting from psoriasis inflammation is also associated with the serotonergic system. The 5‐HT1A receptor should be further explored as a potential therapeutic target for psoriasis pain modulation. Abstract : Imiquimod‐induced psoriasis causes long‐lasting pain in mice. Compound 48/80 and anti‐inflammatory agents attenuate the imiquimod‐induced pain. Long‐lasting nociception is associated with the serotonergic system. A selective 5HT1A receptor agonist alleviates pain‐related behaviour.